Brideshead revisited : the sacred and profane memories of Captain Charles Ryder - Waugh, Evelyn, 1903-1966. (London : Penguin Books, 2011)
Captain Charles Ryder returns to the country estate of Brideshead where he indulges in a sentimental journey that takes him back twenty years to his schoolmates at Oxford and to his memories of the Marchmains.
Adult.
Adult
Keywords: Catholics -- Fiction; Male friendship -- Fiction; Upper class families -- Fiction; Catholics -- Fiction; Family life -- Fiction; Friendship -- Fiction; Upper class -- Fiction; England -- Fiction; England -- Fiction